Suatu Grup pada Struktur Aljabar yang Dibangun dari Senyawa Kimia - Thomas, Abdiel Bellamy; Syahid, Muhammad; Puspita, Nikken Prima (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Group is a set with binary operation and satisfy some axioms. In this paper we want to show groups which constructed from chemical conditions. For the first, there are chemical compounds, between the set from H2, O2, and H2O. Here, we have condition that the set A = H2, O2, H2O is a group with a chemical compounds reaction as it binary operation. Moreover, A is an abelian group as a compensating of the chemical compound. The second, we also have another group from other chemical compound, i.e., acidic compounds. Let B = acid, bases, salt+water is a set and the binary operation * defined as a chemical compounds reaction. We shown that B is an abelian group over *.